Target Gene-Based Association Study of High Mobility Group Box Protein 1 in Intracranial Aneurysms in Koreans - Eun Pyo Hong; Sung Woo Han; Bong Jun Kim; Dong Hyuk Youn; Jong Kook Rhim; Jin Pyeong Jeon; Jeong Jin Park (Brain Sciences, 2024)
Objective: We investigated the effect of high mobility group box 1 (HMGB1) on intracranial aneurysms (IAs) by analyzing single-nucleotide polymorphisms (SNPs) based on genome-wide association study (GWAS) data. HMGB1 mRNA and protein expression levels in plasma were also analyzed. Methods: This study was a comprehensive analysis of a GWAS dataset, including 250 patients with IAs and 294 controls. The HMGB1 gene region was targeted within SNP rs3742305 ± 10 kbp. Multivariate logistic regression analysis determined its association with IAs after adjusting for relevant clinical factors. HMGB1 mRNA expression was analyzed in the plasma of 24 patients selected from the GWAS dataset. The HMGB1 protein was analyzed by Western blotting. Results: A total of seven polymorphisms, including rs1360485, rs185382445, rs2039338, rs1045411, rs3742305, rs2249825, and rs189034241, were observed. Two SNPs, including rs1045411 (UTR-3) and rs3742305 (intron), showed strong linkage disequilibrium (r2 = 0.99). However, none of the seven SNPs associated with IAs had an adjusted p-value of < 0.0016 on multiple comparison analysis. HMGB1 mRNA levels (2−ΔCt) did not differ significantly between patients with IAs and the control subjects [1.07 (1.00–1.15) in patients with IAs vs. 1.05 (0.94–1.12) in controls; p = 0.67)]. Also, no significant difference in the degree of plasma HMGB1 protein expression was seen between the two groups (p = 0.82). Conclusions: The number of SNPs associated with HMGB1 and the degree of HMGB1 mRNA and protein expression were not significantly different between patients diagnosed with IAs and the controls.